Eighty-two per cent of male professional football (soccer) players return to play at the previous level two seasons after Achilles tendon rupture treated with surgical repair - Grassi, A.; Rossi, G.; D'Hooghe, P.; Aujla, R.; Mosca, M.; Samuelsson, K.; Zaffagnini, S. (British Journal of Sports Medicine, 2020)
OBJECTIVE: To evaluate the time to return to playing following acute Achilles tendon rupture (ATR) and surgical repair in professional male football (soccer) players. METHODS: Professional male football (soccer) players who sustained an ATR and underwent surgical repair were identified through internet-based injury reports from January 2008 to August 2018. Only League 1 and 2 players with injuries who had at least 1 year of follow-up from the search date were included. Injury history and time to return to play were retrieved from the public platform transfermarkt.com. For athletes who competed for at least two seasons after returning to play, re-ruptures and number of matches played were reported. RESULTS: 118 athletes (mean age 27.2±7.2 years) were included. 113 (96%) returned to unrestricted practice after a mean of 199±53 days, with faster recovery in players involved in national teams. Return to competition was after a mean of 274±114 days. In the 76 athletes with at least two seasons of follow-up, 14 (18%) did not compete at the pre-injury level during the two seasons following the index injury. Six players (8%) sustained a re-rupture within the first two seasons after return to play; four re-ruptures were in footballers who returned to play <180 days after injury. Age >30 years and re-ruptures had higher odds ratios of not returning to the same level of play. CONCLUSIONS: 96% of professional male football players who underwent surgery to repair an ATR returned to unrestricted practice and then competition after an average time of 7 and 9 months, respectively. However, 18% did not return to the same level of play within the two seasons following their return, with a higher risk in those experiencing a re-rupture.